2012
DOI: 10.5367/te.2012.0130
|View full text |Cite
|
Sign up to set email alerts
|

Crowding Externalities from Tourist Use of Urban Space

Abstract: Popular urban tourist destinations are attracting large numbers of both overnight visitors and excursionists. Since urban cities perform a multitude of functions, the space requirements of tourists can, at times, interfere with those of local users. This paper addresses the issue of disutilities of space congestion through a dichotomous choice experiment model in order to offer a monetary valuation of tourist crowding in urban public space. A resident survey was carried out in the city of Amsterdam in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 67 publications
(87 reference statements)
0
17
0
2
Order By: Relevance
“…The research results are consistent with the dimension of individualism or collectivism. The collectivism evaluates the group as the most important unit, whereas the individualism judges the individual as the most important unit [31,32]. However, another study by Jin and Pearce [5,33] concluded that Europeans and Americans are more tolerant to others' disturbance than Chinese because European and American tourists are more experienced in coping with crowding.…”
Section: Nationality Motivation and Perceived Crowdingmentioning
confidence: 99%
“…The research results are consistent with the dimension of individualism or collectivism. The collectivism evaluates the group as the most important unit, whereas the individualism judges the individual as the most important unit [31,32]. However, another study by Jin and Pearce [5,33] concluded that Europeans and Americans are more tolerant to others' disturbance than Chinese because European and American tourists are more experienced in coping with crowding.…”
Section: Nationality Motivation and Perceived Crowdingmentioning
confidence: 99%
“…Unlike spatial crowding, which has only been reported as an impediment for enjoying the visit, human crowdedness has sometimes been considered as "good crowding", adding up to the local experience. Thus, an interesting finding emerging from this research is that crowding can have not only negative, but also positive consequences on tourist experience and satisfaction [7,9,11,34,56].…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, evidence for the positive association between crowding and tourist satisfaction has also been found, [8,54], particularly when visitors look for hedonic experiences [54], when the level of crowding does not exceed the expectations or when the perception of crowdedness is relatively low [8,55]. In this regard, it can be concluded that a crowding perception is not always negative, but can even contribute to tourist's experience and satisfaction [7,9,11,56].…”
Section: Tourism Crowdingmentioning
confidence: 93%
“…Furthermore, estimating the optimal limit for accommodation saturation is not an end in and of itself, but rather an instrument that can provide continuous, relevant information to those in charge of making decisions related to planning and managing mature tourist destinations. Therefore, it is a management concept which reflects the objectives of managers or those responsible for satisfying tourists and local residents [101].…”
Section: Discussionmentioning
confidence: 99%